Ultrastructural studies on fresh-extended and frozen-thawed goat spermatozoa - KAMAL, KIRON DEEP SINGH; ABDULLAH, RAMLI BIN; KHADIJAH, W E WAN (The Indian Journal of Animal Reproduction, 2023)
Use of routine in vitro maturation, fertilization and culture (IVMFC) protocol in this laboratory with some modifications did not produce satisfactory results in goats due to low cleavage rates. Post-fertilization evaluation of in vitro inseminated oocytes using an inverted microscope indicated absence of sperm penetration into the zona pellucida. It was, therefore, considered necessary to examine the ultrastructure of frozen-thawed sperm in order to determine its integrity and viability. Ultrastructure of freshly ejaculated extended goat sperm was taken as co.ntrol. Electron micrographs of frozen-thawed sperm indicated that inner and outer • acrosomal membranes were undergoing signs of degeneration such as lysis of the membranes specifically at the tip region. Since acrosome plays an important role during fertilization, any changes in its membrane are likely to affect the fertilization rates.